A aplicação dos royalties do petróleo e a efetividade dos direitos fundamentais sociais - Torronteguy, Alessandra Fölzke (2009)
The scope of this work analyses the issue related to royalties from activities related to the oil sector paid to States and Municipalities in Brazil. A connection was established for its application to basic social rights using a dialectic methodology and a qualitative approach. A documental bibliographic research technique was used and an analysis of the decision made by the Federal Supreme Court related to changes in the sector. To bring the work closer to reality, information was collected from professionals of the oil area and in the royalties application inspection. An analysis was carried out related to the oil interferences on the society, their origin and history presenting its economic and social power. Later, a scenario was developed about the legal history that regulates the issue, showing the legislative omission, which ended up as a way of violating the principle that prevents social retrogress. The importance of the public administrator and other sectors of the Civil Society has been highlighted here, regarding the conception, preparation and implementation of public policies to make social rights effective, catering to all generations’ needs. In view of values gathered as royalties, and legislative omission regarding the use of the sources in the State of Espirito Santo, an organization was created called Regional Inequalities Reduction Fund, sharing out part of the State income to municipalities that do not produce oil. According to the federal principle and the State and Municipalities autonomy, each Municipality receiving the royalties directs its use to more impoverished areas, thus making the application different for each Municipality. Many times the consequences of the oil industry cannot be easily noticed and this can lead to an ideological acceptance favorable to the interests of the sector, influencing political decisions related to the use of the royalties in the Municipalities. It is, then, fundamental that the state action is based on principles directing its acts, not simply following the order in case of legislative omission, acting in favor of the immediate application of fundamental social rights. The conclusion of the present study deals with the way the royalties application has been used and the role of the Treasury Department and Public Ministry as institutions in charge of the inspection and defense of collective and social interests making royalties a social instrument.